Xigaza Monday: Enhancing Xitsonga Language Preservation through Artistic Expression - Tiyiselani Ndukwani (Asosiasi Dosen Perguruan Tinggi Islam, 2025)
The preservation of indigenous languages remains a critical concern in multilingual societies, particularly in South Africa, where minority languages like Xitsonga face challenges including language shift, cultural assimilation, and limited representation in mainstream media. This study investigates the role of Xigaza Monday, a community-driven initiative that celebrates and promotes the Xitsonga language through artistic expression, focusing on music, dance, and community performances. The study employed qualitative research methods, including participant observation, semi-structured interviews, and content analysis of performances and social media content. A total of thirty participants were interviewed, comprising 18 youth performers, 7 event organizers, and 5 cultural experts. Data were analyzed thematically to identify key patterns in language use, cultural engagement, and participants’ perceptions of the event. The findings indicate that Xigaza Monday fosters language pride, strengthens intergenerational transmission of Xitsonga, and provides an informal platform for linguistic creativity. Participants exhibited knowledge of Xitsonga vocabulary, idiomatic expressions, and proverbs, while younger attendees demonstrated adaptive use of language in contemporary artistic forms. Challenges identified include limited outreach, infrastructural constraints, and the need for sustained community involvement. The study concludes that initiatives such as Xigaza Monday play a pivotal role in preserving the Xitsonga language, maintaining cultural continuity, and engaging youth. Recommendations include expanding digital presence, formal partnerships with educational institutions, and systematic documentation of performances for linguistic research.